Information ecosystem related to adults` healthy lifestyle monitoring - A. Musin, Oleg (2020)
This article discusses the problem of providing adults with reliable, relevant and timely information that allows them to organize their activities: the regime of work and rest in accordance with the goals of a healthy lifestyle and health correction. The goal is to determine the criteria and components of an information resource that will be adequate to the goals of keeping health of adults. The leading approaches to the health care mass media research are: structural-analytical, personality-oriented and cultural approaches. Research methods: analysis and synthesis of scientific and methodological literature and the information environment on the problems of the population health improving and methods of mathematical data processing. The article presents the results of determining the criteria for monitoring the information ecosystem on a healthy lifestyle, among these criteria the following were identified: the scientific validity of information, targeting, social significance and dialogue. Also, data portals that contribute to the solution of certain tasks of the adult population health improving were identified. The authors designed and implemented the informational and educational portal “3 youth” which is aimed at the integrated implementation of the basic health-improving needs of the adult population, taking into account the interconnection of health components: physical, mental, social. The results proving the effectiveness of using the authors' portal to ensure a healthy lifestyle for adults are presented and discussed. The article will be useful to adults who want to lead a healthy lifestyle with the support of the information resources, teachers and trainers working with people of mature age. This article is also useful for teachers of the Faculty of Physical Education who plan to promote a healthy lifestyle among different age categories.